2015
DOI: 10.1038/srep12228
|View full text |Cite
|
Sign up to set email alerts
|

The Balance of Expression of Dihydroflavonol 4-reductase and Flavonol Synthase Regulates Flavonoid Biosynthesis and Red Foliage Coloration in Crabapples

Abstract: Red leaf color is an attractive trait of Malus families, including crabapple (Malus spp.); however, little is known about the molecular mechanisms that regulate the coloration. Dihydroflavonols are intermediates in the production of both colored anthocyanins and colorless flavonols, and this current study focused on the gene expression balance involved in the relative accumulation of these compounds in crabapple leaves. Levels of anthocyanins and the transcript abundances of the anthocyanin biosynthetic gene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 57 publications
5
71
0
Order By: Relevance
“…We previously reported that the anthocyanin concentration in ever-red leaves, was significantly higher than that in ever-green leaves17, and that a competitive relationship between anthocyanin and flavonol is important for leaf coloration46. We characterized PAs accumulation patterns during five leaf developmental stages (1–5) of the ever-red leaf cultivar ‘Royalty’ and the ever-green leaf cultivar ‘Flame’, using high pressure liquid chromatography (HPLC) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that the anthocyanin concentration in ever-red leaves, was significantly higher than that in ever-green leaves17, and that a competitive relationship between anthocyanin and flavonol is important for leaf coloration46. We characterized PAs accumulation patterns during five leaf developmental stages (1–5) of the ever-red leaf cultivar ‘Royalty’ and the ever-green leaf cultivar ‘Flame’, using high pressure liquid chromatography (HPLC) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, up-regulation in the expression of the PAs regulator McMYB12b significantly enhanced the accumulation of PAs, and inhibited the biosynthesis of anthocyanins (Figs 6A and 8). We deduced from these data that there is a metabolic balance between flavonol and anthocyanin biosynthesis46, and that the anthocyanin and PAs biosynthetic pathways have a competitive relationship in crabapple leaves. The massive expression of McCHS , an upstream enzyme in flavonoids biosynthesis, may promote the accumulation of anthocyanins in McMYB12a -overexpression lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon silencing of Nt FLS in tobacco by RNAi, the content of flavonol in transgenic plants decreased by 25 – 93%, while the contents of catechins, epicatechin and epigallocatechin increased . Overexpression of McFLS in Malus crabapple using transient expression systems revealed significant increase in flavonol content at the injection site and significant decrease in anthocyanin content . Thus, there was competitive relationship between production of flavonols and anthocyanins.…”
Section: Discussionmentioning
confidence: 97%
“…Stem tips were used as explants and the explants of the two cultivars were harvested from 1 year-old branches before spring bud germination. Stem tip sections were rinsed with water for 2 h and disinfected with 0.15 % HgCl 2 for 8 min 2.0-3.0 mm long stem tips were cultured on Murashige and Skoog (MS) medium supplemented with 0.1 mg/L 6-BA and 2.0 mg/L 2, 4-D at 23°C for a 16 h light (200 lmol s -1 m -2 )/8 h dark period for 60 days, prior to Plant Cell Tiss Organ Cult VIGS infiltration (Tian et al 2015a). After infiltration, all crabapple tissue culture plantlets were rinsed with distilled water and cultured in MS medium supplemented with 50 mg/L kanamycin and 100 mg/L sodium cefotaxime.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%